Definition of the EGTA-independent interface involved in the serum gelsolin-actin complex. - Feinberg, J (1993)
The gelsolin-actin complex in the presence of Ca2+ revealed at least three interacting sites on the gelsolin molecule located in the S1, S2-3, and S4-6 domains. In the presence of EGTA, the N-terminal domain of gelsolin is known to be involved. However, the corresponding site on the surface of actin is poorly defined. The present result locates the Ca(2+)-independent plasma gelsolin-binding site on the actin surface. Natural and synthetic actin peptides were tested for their possible interaction with gelsolin and monitored by fluorescence anisotropy measurements and e.l.i.s.a. The interface was thus located within the 360-372 actin sequence near the C-terminal extremity. In addition, we used a chymotryptic digest of gelsolin and determined that its N-terminal domain (S1) was implicated in this interface. We conclude that the interaction of the 41-126 region of plasma gelsolin is the counterpart of the 360-372 sequence in subdomain 1 of actin.